Political Ideology and the Intragenerational Prospect of Upward Mobility - Maite D. Laméris; Harry Garretsen; Richard Jong-A-Pin (Center for Economic Studies and ifo Institute (CESifo), 2018)
We examine the effect of prospects of upward mobility (POUM) on the support for redistribution in an intragenerational context. In this context, existing literature so far fails to consider the potential indirect channel via political ideology through which mobility expectations affect redistributive preferences. We address this by including an interaction between income mobility and political ideology, such that the POUM-effect is allowed to vary with political beliefs. We find a robust POUM-effect that is conditional on political preferences. Only for right-wing individuals expected upward income mobility negatively affects support for redistribution. Left-wing individuals on the other hand prefer redistribution, regardless of expected upward income movements.
Keywords: D30; D72; J69; 330; the POUM-effect; political ideology; income mobility; redistribution; preferences